Pengaruh Pemberian Pakan Rucah dan Pakan Pellet Terhadap Pertumbuhan Juvenil Ikan Kerapu Bebek (Chromileptes altivelis) - Ikhsan Wamnebo; Muhammad Ali Ulat (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2021)
This study aims to determine the effect of feeding trash and artificial feed on the growth and survival of juvenile duck grouper (Chromileptes altivelis). The research was conducted at the Ambon Marine Cultivation Center. The study consisted of 2 treatments, namely: Treatment A (trash feed) and Treatment B (artificial feed). The results showed that the growth rate and survival rate of juvenile duck grouper (Chromileptes altivelis) fed trash showed that the final average length was 10.56 cm and the final average weight was 11.52 grams, while the final average length was 11.52 grams. grouper duck fed artificial feed was 9.43 cm and the final average weight was 8.44 grams. The survival rate of grouper ducks given either artificial feed or trash feed resulted in a high survival rate of 100%.